Recommendations for environmental risk assessment of gene drive applications for malaria vector control - Connolly, J; Mumford, J; Glandorf, D; Hartley, S; Lewis, O; Evans, SW; Turner, G; Beech, C; Sykes, N; Coulibaly, M; Romeis, J; Teem, J; et al. (BioMed Central, 2022)

(untitled)
Building on an exercise that identified potential harms from simulated investigational releases of a population suppression gene drive for malaria vector control, a series of online workshops identified nine recommendations to advance future environmental risk assessment of gene drive applications.